Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.37284/eajass.4.1.449
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Delinquency and Crime Nairobi Slum Areas, Kenya

Abstract: Juvenile delinquency has become an urgent concern for sociologists across the globe because it is a significant predictor of a possible increase in criminal activity among our growing population. A juvenile is a person who is under the age of ordinary criminal prosecution, which is normally 17 years. The increase in the incidence of juvenile delinquency implies that if measures are not taken in place, there are possibilities of the situation running out of hand. Juvenile delinquency can be considered as social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Notably, drugs impair teenagers' judgment and increase their impulsivity, which in turn increases their propensity to engage in criminal behaviour (Haylock et al, 2020). Additionally, a lifestyle associated with the use of drugs exposes teenagers to criminal networks, thereby normalizing illegal activities and providing them with opportunities to engage in criminal activities (Wa Teresia, 2021), Various community factors have also been linked to the acquisition of delinquency. The crime rates in the neighbourhood and the presence of criminal gangs increase the exposure of teenagers to criminal behaviour (Mahmoodi et al, 2021).…”
Section: Socio-economic Factors Causing Teenage Delinquency In Slumsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, drugs impair teenagers' judgment and increase their impulsivity, which in turn increases their propensity to engage in criminal behaviour (Haylock et al, 2020). Additionally, a lifestyle associated with the use of drugs exposes teenagers to criminal networks, thereby normalizing illegal activities and providing them with opportunities to engage in criminal activities (Wa Teresia, 2021), Various community factors have also been linked to the acquisition of delinquency. The crime rates in the neighbourhood and the presence of criminal gangs increase the exposure of teenagers to criminal behaviour (Mahmoodi et al, 2021).…”
Section: Socio-economic Factors Causing Teenage Delinquency In Slumsmentioning
confidence: 99%
“…Teenagers may adopt delinquent behaviour as a coping mechanism for their emotional stress. They may also adopt criminogenic behaviour as a way of self-medicating, mainly when they are engaged in substance and drug abuse (Wa Teresia, 2021). Alternatively, this also becomes a way to vent their frustration, which may emanate from their impoverishment and desperation at home (Pereda et al, 2022).…”
Section: Individual Factors Influencing Teenage Delinquency In Slumsmentioning
confidence: 99%
“…In Kenya, several studies have examined the relationship between socio-economic factors and youth crime. For instance, a study by Ndikaru (2021) identified poverty and lack of educational opportunities as significant predictors of youth crime in Nairobi, with family problems and peer influence also contributing to youth delinquency. Another study by Thuku (2017) explored the link between unemployment and crime among youths in Nyeri, finding Licensed Under Creative Commons Attribution (CC BY-NC) that unemployment was a significant predictor of youth crime, and poverty and lack of education played crucial roles in contributing to crime.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini tampak selaras dengan penelitian yang dilakukan oleh Wa Teresia (2021), yang mengungkap bahwa lingkungan tempat remaja dibesarkan sangat erat kaitannya dalam mempengaruhi perilaku delinkuen. Ada korelasi yang kuat antara keterlibatan remaja terhadap peristiwa sejarah dan pengalamanpengalaman yang terbentuk di dalam lingkungan tempat tinggal di dalam komunitas(Wa Teresia, 2021). Dengan demikian, dalam mengidentifikasi faktor risiko kenakalan remaja perlu mempertimbangkan konteks sosial yang lebih luas di mana remaja tinggal dan bertindak.Penelitian ini menemukan fakta bahwa perubahan perilaku remaja menuju perilaku antisosial banyak terjadi setelah penggusuran.…”
unclassified